Perceived oppression and online support for COVID-19 non-compliance: the 2021 Trieste port protests - Arletti, Alberto; Candiracci, Alessandro; Cottone, Paolo Francesco (Frontiers in Political Science, 2025)
The enforcement of COVID-19 containment measures, such as lockdowns or mandatory vaccination, can have significant consequences for both public health and the economic stability of institutions. As a result, widespread non-compliance poses a particular challenge for governments. In October 2021, workers in Trieste, Italy, blocked the city's commercial port in protest against new restrictions, triggering large-scale demonstrations and an explosion of related activity on Twitter. We analyze this unique case of mass non-compliance by collecting tweets about the protests and applying sentiment analysis, topic modeling, opinion analysis, user clustering, and diffusion modeling. Our findings reveal a strong connection between online support for non-compliance and emotions such as anger and mistrust, particularly toward the government, which are often framed as reactions to perceived injustice or oppression. The results suggest that social media played a key role in amplifying and normalizing non-compliant sentiment. While this study does not make normative claims about the legitimacy of either side, it offers a methodological lens for understanding how polarizing debates unfold online. This approach can also be extended to other divisive issues such as climate policy, military conflict, or artificial intelligence, or in general with regards to contrasting or diverse opinions discussed online. By better understanding the motivations and narratives of non-compliers, institutions may be better equipped to foster dialogue and reduce reliance on force.